Nanotubos de carbono substitucionados com monômeros e dímeros de titânio: uma aproximação de primeiros princípios - Santos, Elton José Gomes dos (2006)
In this work we have studied, through ab initio approaches, some ways to obtain titanium monomers and dimers substitutioned on metallic or semiconducting carbon nanotubes. We show the most possible substitutional routes for impurity agregation in the nanotube surface, seen the closed relation between the vacancy number upon the carbon wall and the impurity metallic concentration put in each site. We find this sistematic doping way produce many pronounced changes upon the main electronic and structural tube properties. Where it is now possible to produce metal-ligante complex, dependending on the tube defects production and the most stable geometric configuration of the metallic impurities on the tube carbon lamela. It might be utilized as an agregation reactive center for new structures at the titanium atoms and the hibrid structure formation, so evidence in many functionalization plays. The spin polarization energy total calculations were perfomed with the SIESTA code - Spanish Initiative for Eletronic Simulations with Thousands of Atoms, what it today consist in the art state inside the ab initio calculations for algorithm that has a order-N materials simulation. The results can be obtained in easier way than the plane wave calculation because the cheap computational price and the high velocity. In addition, a serious electronic study is made on electronic band structure, density os states, localized charge density contour plot in every level, the Mulliken population and the most stable geometric configuration of these systems.